MiR-24-3p Inhibits the Progression of Pancreatic Ductal Adenocarcinoma Through LAMB3 Downregulation - Huang, Wenjie; Gu, Jianyou; Tao, Tian; Zhang, Junfeng; Wang, Huaizhi; Fan, Yingfang (Frontiers in Oncology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is associated with several genetic syndromes. However, the molecular mechanism underlying PDAC progression is still unknown. In this study, we showed that Laminin Subunit Beta 3 (LAMB3) was aberrantly overexpressed in PDAC and closely associated with the overall survival rate of patients with PDAC. Functional studies demonstrated that LAMB3 played important roles in cell proliferation, cell cycle, and invasion capacity. Using bioinformatics analysis, we determined that miR-24-3p was an upstream miRNA of LAMB3, and further experiments verified that miR-24-3p regulated LAMB3 expression in PDAC cells. Dual-Luciferase report system demonstrated that miR-24-3p directly targeted the LAMB3 3'UTR, and FISH assay confirmed that miR-24-3p and LAMB3 mRNA mostly resided in cytoplasm, accounting for their post-translational regulation. Rescue assay demonstrated that miR-24-3p exerted its anti-cancer role by suppressing LAMB3 expression. Finally, by using subcutaneous xenotransplanted tumor model, we demonstrated that miR-24-3p overexpression inhibited the proliferation of PDAC by suppressing LAMB3 expression in vivo. Collectively, our results provide evidence that miR-24-3p/LAMB3 axis plays a vital role in the progression of PDAC and indicate that miR-24-3p/LAMB3 axis may represent a novel therapeutic strategy for PDAC.